Self-assembled nanoparticles of dextrin substituted with hexadecanethiol - Gonçalves, Catarina (2007)
Amphiphilic molecules, such as surfactants or lipids, spontaneously self-assemble in water, forming self-aggregates, such as micelles, bilayer membranes, tubes and vesicles. Amphiphilicity of biopolymers is one of the most important factors for their self-organization in water. Among the different types of amphiphilic polymers, water-soluble polymers with hydrophobic molecules grafted on side chains have received special attention. By self-assembling, the hydrophobic segments are segregated from the aqueous exterior, to form an inner core surrounded by hydrophilic chains. Polymeric micelles or nanoparticles with hydrophobic core and hydrophilic shell are thus prepared. This kind of structure is suitable for trapping hydrophobic substances, such as fluorescent probes, proteins, and hydrophobic pharmaceuticals. The amphiphilic molecule dextrin-VA-SC16 (dexC16) was synthesized and studied in this work. DexC16 has a hydrophilic dextrin backbone with grafted acrylate groups (VA), substituted with hydrophobic 1-hexadecanethiol (C16). A versatile synthetic method was developed allowing to control the dextrin degree of substitution with the hydrophobic chains (DSC16, number of alkyl chains per 100 dextrin glucopyranoside residues). Materials with different DSC16 were prepared and characterized using 1H NMR. DexC16 self assembles in water through association of the hydrophobic alkyl chains, originating nanoparticles. The nanoparticles properties were studied by dynamic light scattering (DLS), fluorescence spectroscopy and atomic force microscopy (AFM). The peptide tufstin was grafted in the surface of nanoparticles. The effetc of the peptide in addressing the particles to macrophages, in invitro assays, will be shown.